PEMBELAJARAN BERBASIS VIDEO PADA MATERI IPA TENTANG SISTEM PENCERNAAN MANUSIA KELAS V DI SD NEGERI 1 BANDA ACEH PADA MOTIVASI BELAJAR SISWA - Raudhatul Muna; Siti Mayang Sari; Lili Kasmini (Jurnal Dikdas Bantara, 2024)
In the learning process in elementary schools, obstacles in learning are very often found. Obstacles can make it difficult for students to understand the material delivered by the teacher because the explanations given are too abstract so motivation to study the human digestive system is still relatively low. The aim of this research is to increase students' motivation to learn. Science material on the human digestive system through video-based learning. This research utilized a descriptive research design and qualitative methodology. With three data acquisition techniques, namely documentation, interviews and observation. Based on motivation, research shows that the use of video-based learning media can convey the content of the learning process very clearly so as to increase students' motivation to learn. The encouragement for student learning is by using video-based learning media, the availability of educational materials can make everything simpler. in conveying the content of the learning that students will learn. It is hoped that the use of the designed teaching videos can increase students' learning motivation in learning the science of the human digestive system.